A physician's approach and experience of managing patients with diabetes during COVID‐19. (8th April 2021) - Ruslan, Aliya; Williams, David M; Purnell, Oliver; Edwards, Rhodri; Peter, Raj; Stephens, Jeffrey W; Chudleigh, Richard
Abstract: Since the start of the COVID‐19 pandemic, the vulnerability of people with diabetes has been recognised with a greater risk of morbidity and mortality compared to the general population. The outcomes associated with diabetes may be a consequence of an impaired immune response, presence of composite comorbidities or the multi‐organ infectivity of SARS‐CoV‐2 affecting the pancreas. Emerging evidence suggests that both acute and chronic hyperglycaemia can exacerbate the clinical consequences of COVID‐19. Thus, the role of health care professionals in the observation and management of glucose control is increasingly recognised in people with diabetes in both the acute and chronic setting. In this review, we highlight the key biological implications of SARS‐CoV‐2 infection in people with diabetes, the clinical outcomes of COVID‐19 in people with diabetes and management principles with respect to glucose control including our local experiences. Copyright © 2021 John Wiley & Sons.